Marcinkiewicz multiplier and Littlewood-Paley type theorems in Smirnov-Orlicz classes - Jafarov, S.Z. (Romanovsky Institute of Mathematics of the Academy of Sciences of the Republic of Uzbekistan, 2025)
Let G be finite Jordan domain bounded a Dini smooth curve Γ in the complex plane. Marcinkiewicz multiplierand Littlewood-Paley type theorems in Smirnov-Orlicz classes, defined in domain G, are proved. © 2025, Romanovsky Institute of Mathematics of the Academy of Sciences of the Republic of Uzbekistan. All rights reserved.
Keywords: Dini-Smooth Curve; Faber Series; Faber-Laurent Series; Littlewood-Paley Theorem; Marcinkiewicz Multiplier Therem; Orlicz Spaces; Smirnov Spaces